Design of Casocidin-II Mutation Variants as Antibacterial Candidates against Helicobacter pylori using Bioinformatic Approaches - Prasetya, Yulianto Ade; Kok, Tjie (MPI (Media Pharmaceutica Indonesiana), 2025)
Helicobacter pylori infects about 50% of the global population, with high prevalence in Indonesia, particularly in East Nusa Tenggara (51.4%) and Papua (30.7%). If untreated, this infection can cause gastritis, ulcers, and even gastric cancer. Due to rising antibiotic resistance to this bacterium, alternative treatments are needed. Casocidin-II, an antimicrobial peptide from cows milk (Bos taurus), has antibacterial potential but it is unstable in acidic environments, making it ineffective against H. pylori, which colonizes in the stomach. This research aims to design and analyze Casocidin-II mutations using bioinformatic approaches to improve stability without reducing antibacterial activity. Mutations were conducted using I-Mutant 2.0, and structural modeling was done with PEP-FOLD4. Physicochemical properties were analyzed with ExPASy, and the binding affinity to H. pylori BabA receptor was evaluated using HADDOCK. Molecular interactions were visualized with ChimeraX. Eight stable Casocidin- II mutants (CAS1–CAS8) were identified, with CAS3 and CAS5 showing the best stability, hydrophilicity, and aliphatic index. Docking results showed CAS3 and CAS7 had the highest binding affinities, -121.70 kcal/mol and -123.24 kcal/mol, respectively. CAS3, with the sequence KTKLTVEEKNRLNFLKKISQRYQKFALPQYLKTVYQHQK, was the most effective in inhibiting H. pylori growth and is a strong candidate for further laboratory testing. Besides its high affinity and activity, CAS3’s amino acid profile enhaces target binding and membrane penetration. This research demonstrates that bioinformatics can be used in designing mutation varians to enhance peptide stability and antibacterial properties. CAS3 is a promising alternative to conventional antibiotics for H. pylori treatment, pending further experimental validation.